Reciprocal modulation of internal and external factors determines individual movements. (5th October 2012) - Martin, Jodie; van, Bram; Revilla, Eloy; Blanchard, Pierrick; Dray, Stéphane; Quenette, Pierre‐Yves; Allainé, Dominique; Swenson, Jon E.; Fryxell, John
Summary Movement is fundamental to individual and population dynamics, as it allows individuals to meet their basic requirements. Although movement patterns reflect interactions between internal and external factors, only few studies have examined the effects of these factors on movement simultaneously, and they generally focused on particular biological contexts (e.g. dispersal, foraging). However, the relative importance of these factors in driving individual routine movements might reflect a species' potential flexibility to cope with landscape changes and therefore buffer their potential impact on fitness. We used data from GPS collars on Scandinavian brown bears to investigate the relative role of these factors, as well as an additional factor (period of the year) on routine movements at two spatial scales (hourly and daily relocations). As expected, internal factors played a major role in driving movement, compared to external factors at both scales, but its relative importance was greater at a finer scale. In particular, the interaction between reproductive status and period of the year was one of the most influential variables, females being constrained by the movement capacity of their cubs in the first periods of the year. The effect of human disturbance on movement was also greater for females with cubs than for lone females. This study showed how reciprocal modulation of internal and external factors is shaping space use of brown bears. We stress that these factors should be studied simultaneously to avoid the risk of obtaining context‐dependent inferences. Moreover, the study of their relative contribution is also highly relevant in the context of multiple‐use landscapes, as human activities generally affect the landscape more than they affect the internal states of an individual. Species or individuals with important internal constraints should be less responsive to changes in their environment as they have less freedom from internal constraints and should thus be more sensitive to human alteration of the landscape, as shown for females with cubs in this study.